Analysis of the Thermo-Mechanical Behavior of a Multi-Plate Clutch during Transient Operating Conditions Using the FE Method - Thomas Schneider; Maximilian Dietsch; Katharina Voelkel; Hermann Pflaum; Karsten Stahl (Lubricants, 2022)
Failures of multi-plate clutches must be reliably excluded due to safety-critical functionalities in the drive train. The main reason for failures of multi-plate clutches due to long-term and spontaneous damage is thermal damage. In this paper, a parameterizable two-dimensional finite element model is developed and validated for damage prevention and for analyzing the thermo-mechanical behavior of a clutch in transient operation. Both numerical verification and validation with experimental results are very good despite the simplifications in the model. Subsequently, the temperature and pressure distribution of the individual friction areas is determined. The results show that the maximum temperatures tend to occur at the outer diameter of the friction area. The pressure distribution is very homogeneous. In a parameter study, the influence of Young’s modulus of the friction lining, the thermal conductivity of the friction lining, and the steel plate thickness on the temperature and pressure behavior in the clutch is investigated. Although the Young’s modulus of the friction lining influences the pressure distribution in the friction contact, the temperature behavior is only slightly changed by the variation of the elastic modulus due to the load case. The thermal conductivity of the lining and steel plate thickness have a strong influence on the temperature level in the clutch. However, the distribution of pressures is still very homogeneous compared to the reference model.